2005
DOI: 10.1079/phn2004698
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the temporal intake of cereal and dairy products in Irish adults: implications for developing food-based dietary guidelines

Abstract: Objectives: To analyse the temporal distribution of the intake of cereal and dairy products in the Republic of Ireland. Design: The North/South Ireland Food Consumption Survey established a database of habitual food and drink consumption using a 7-day food diary. The database also recorded the time and day of food consumption. Mean intakes of cereal and dairy products were calculated for time of the day and day of the week. Results: At the weekend, the percentage of consumers decreased for nearly all cereal an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…A different pattern of intake throughout the day was present for those that consumed cakes. 11 The present study contributes evidence for moderate daily noon and evening eating events associated with higher diet quality.…”
Section: Discussionsupporting
confidence: 54%
See 4 more Smart Citations
“…A different pattern of intake throughout the day was present for those that consumed cakes. 11 The present study contributes evidence for moderate daily noon and evening eating events associated with higher diet quality.…”
Section: Discussionsupporting
confidence: 54%
“…11,43,50 Intake at certain times of the day may be associated with foods that are recommended for reduction in the dietary guidelines and diets that are less supportive of overall health. Using dietary data from the 1946 British birth cohort, Burke et al 11 found consistent mealtime peaks for morning, afternoon, and early evening for the consumers of white bread, wholemeal bread, total cereals, reduced and full-fat milk and total dairy. A different pattern of intake throughout the day was present for those that consumed cakes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations